Comparison of Routine Hematology Test Results: Venous Blood versus Capillary Blood Using a Hematology Analyzer in the Juanda Kuningan Hospital Laboratory - Wandriono, Andri; Rizki Nurul Aeni, Suci; Nuralifah Anggraeni, Ayu (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
Hematology tests using automated equipment typically use venous blood samples. However, in certain cases where venous blood cannot be obtained, such as when veins cannot be clearly palpated due to obesity or burns at the sampling site, capillary blood samples can be used to address these issues. To understand the differences in venous and capillary blood test results using a hematology analyzer, capillary blood can be used as an alternative. This study will be a comparative study with a cross-sectional design to examine the comparison of venous and capillary blood in hemoglobin levels, leukocyte counts, erythrocyte counts, and platelet counts. The study population consisted of 30 venous blood samples and 30 capillary blood samples taken from outpatients in the Juanda Kuningan Hospital laboratory. Research Results: The results showed that routine hematology tests using venous blood yielded an average leukocyte count of 11.54 × 103/µL. The average hemoglobin was 12.47 g/dL. The average hematocrit was 35.28%. The average erythrocytes were 4.24 106/uL and the average platelets were 308 103/uL. The results of routine hematology examinations using capillary blood showed that the average leukocyte examination results were 11.39 103/ul, the average hemoglobin was 12.33 g/dL. The average hematocrit was 35.04%, the average erythrocytes were 4.15 106/uL and the average platelets were 299 103/uL. There was no significant difference in the results of leukocyte, hemoglobin, hematocrit and platelet examinations using venous blood and capillary blood, while there was a significant difference in the results of erythrocyte examinations using venous blood and capillary blood.